2014
DOI: 10.4081/jlimnol.2014.857
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physico-chemical and microbiological parameters in the monimolimnion of a forest meromictic lake

Abstract: This study describes the impact of environmental factors on prokaryotic community structure and dominant bacterial groups in the monimolimnion of a meromictic lake. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Some recent studies showed that environment is crucial in the formation of planktonic microbial communities, and that it is predominantly the local environment that regulates community composition [ 41 , 43 , 53 , 54 ]. For ninety-eight shallow lakes located in three European regions there is strong evidence that species sorting in response to local environmental factors is a key determinant of the taxon composition of aquatic bacterial communities over a very broad range of spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies showed that environment is crucial in the formation of planktonic microbial communities, and that it is predominantly the local environment that regulates community composition [ 41 , 43 , 53 , 54 ]. For ninety-eight shallow lakes located in three European regions there is strong evidence that species sorting in response to local environmental factors is a key determinant of the taxon composition of aquatic bacterial communities over a very broad range of spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple stepwise regression analysis for the Zapadłe lake in North-Eastern Poland showed the following factors determined prokaryotic abundance: conductivity, TN, depth, temperature, Fe, DOC and N org ( r 2 = 0.89, P < 0.05), while conductivity, TOC, H 2 S and PO 4 influenced prokaryotic biomass at r 2 = 0.92 ( P < 0.05). Canonical correspondence analysis (CCA) indicated that conductivity, H 2 S, DON, TOC, DOC, N tot , N org , NH 4 , P tot , P org , PO 4 , and Mn explained changes in bacterial community structures in June and September, while the most important measured factor in November was temperature [ 53 ]. For the intertidal coast of the Río de la Plata estuary (Argentina) were found that the plankton community assemblage was significantly modified by high eutrophication levels along the intertidal southwest coast of the estuary [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meromictic lakes are also characterised by a small increase in monimolimnion temperature [16], which remains stable throughout the year [17]. The mixolimnion and the monimolimnion are separated by the chemocline, in which the concentrations of chemical compounds, dissolved mineral salts, and organic matter [9], including microorganisms, increase rapidly [2,3,[18][19][20][21][22][23]. Tartari et al [24] provide the example of Lake Idro in Italy, where the main water layers are not separated by a chemocline.…”
Section: Introductionmentioning
confidence: 99%
“…Lake water is mixed due to differences in water density. The stability of stratified lakes is dependent on water density as a function of temperature, and it can be reinforced by the accumulation of soluble salts in the deepest layers, which increase the water density [1,22,25,26]. In limnological research, mineralisation is only taken into account in evaluations of water density in saline lakes.…”
Section: Introductionmentioning
confidence: 99%
“…A recognized disadvantage of this restoration technique is its impact on downstream waters, including eutrophication, oxygen depletion and odour development (Nürnberg, 2007). This method involves the removal of oxygen-deficient water from the lake's hypolimnion layer, which is characterized by significant fertility and the presence of methane, hydrogen sulphide and decomposable organic matter, to the receiving body, usually a river (Cooke et al, 1982;Klapper, 1991;Nürnberg, 2007;Górniak et al, 2014;Zamparas and Zacharias, 2014). Hypolimnion water pollutes the watercourse into which it is discharged, and it induces periodic changes in hydrochemical and biological conditions (Elloumi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%